Integrasi Teori Diyat Perspektif Hukum Pidana Islam dengan Pendekatan Restorative Justice dalam Sistem Hukum Pidana Indonesia - Alpaten, Ulil Albab Al Aulia; Harahap, Rustam Dahar Karnadi Apollo (Fakultas Syariah Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
This study explores the integration of the Diat theory in Islamic criminal law with the Restorative Justice (RJ) approach in the Indonesian criminal justice system. Diat is a form of compensation granted to victims or their families in certain criminal cases, aiming to promote justice and social reconciliation. Meanwhile, RJ is emerging in Indonesia as an alternative dispute resolution focusing on healing victims and restoring social harmony. This research aims to identify the conceptual intersection between both systems and develop an integrative model applicable to the national legal framework. Using a normative and literature-based approach, the findings indicate that Diat principles can be aligned with RJ mechanisms, especially in non-litigation and participatory resolutions. This integration is expected to strengthen a more humane, equitable, and restorative criminal justice system in Indonesia.